2016
DOI: 10.1126/sciadv.1600883
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Isthmus of Panama

Abstract: Independent evidence from rocks, fossils, and genes converge on a cohesive narrative of isthmus formation in the Pliocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
598
2
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 701 publications
(679 citation statements)
references
References 204 publications
31
598
2
8
Order By: Relevance
“…Surprisingly, Rhinebothrium was not found parasitizing the Pacific host, S. pacifica, despite the common pattern of pairs of transisthmian species cited above for cestodes and reported for many other lineages of Metazoa (Marques et al 1996;Lessios 2008;O'Dea et al 2016). In addition, since members of Rhinebothrium are commonly found in batoids (Linton 1890;Brooks 1977;Friggens & Duszynski 2005;Reyda & Marques 2011;Marques & Reyda 2015;Golestaninasab & Malek 2016), we assume that the lack of members of this genus in this host could be an artifact of sample size and/or biogeographical representation.…”
Section: Discussionmentioning
confidence: 68%
“…Surprisingly, Rhinebothrium was not found parasitizing the Pacific host, S. pacifica, despite the common pattern of pairs of transisthmian species cited above for cestodes and reported for many other lineages of Metazoa (Marques et al 1996;Lessios 2008;O'Dea et al 2016). In addition, since members of Rhinebothrium are commonly found in batoids (Linton 1890;Brooks 1977;Friggens & Duszynski 2005;Reyda & Marques 2011;Marques & Reyda 2015;Golestaninasab & Malek 2016), we assume that the lack of members of this genus in this host could be an artifact of sample size and/or biogeographical representation.…”
Section: Discussionmentioning
confidence: 68%
“…However, we note that the timing of Corvidae-Laniidae split of the recent phylogeny of songbirds based on~5000 loci by Moyle et al [70] coincides with our estimate for the same node (not shown here). Moreover, our time estimates for the MRCA of the South American genera (2.8−2.0M years for Cyanolyca, and 2.3−1.7M years for Cyanocorax) make intuitive sense, since dispersal of theses clades from Mesoamerica into South America should postdate the emergence of the Isthmus of Panama, around 2.8 M years ago [71]. However, we emphasize that our time estimates are rough estimates of actual time and must be considered with caution.…”
Section: Discussionmentioning
confidence: 87%
“…For all models, we created two time intervals, one from 0 to 5 Ma (approximating the time of close proximity of Central and South America, culminating in final closure of the Isthmus of Panama about 3 Ma [65]) and 5 -25 Ma (reduced proximity). For dispersal multipliers, we used a value of 1.0 for all adjacent, connected areas, 0.5 for southern Central America and South America prior to 5 Ma, and 0.01 for distant unconnected areas.…”
Section: (F ) Biogeographic Analysismentioning
confidence: 99%